Evaluation of herb-drug interaction of a polyherbal Ayurvedic formulation through high throughput cytochrome P450 enzyme inhibition assay. (2nd February 2017) - Pandit, Subrata; Kanjilal, Satyajyoti; Awasthi, Anshumali; Chaudhary, Anika; Banerjee, Dipankar; Bhatt, B.N.; Narwaria, Avinash; Singh, Rahul; Dutta, Kakoli; Jaggi, Manu; Singh, Anu T.; Sharma, Neena; et al.
Abstract: Ethnopharmacological relevance: Arishtas are Ayurvedic formulation made with decoction of herbs. Arjunarishta formulation is being used in Ayurveda for cardio-protective activity. Ashwagandharishta formulation possesses antioxidant, anti-atherosclerotic and anti-stress properties. Ridayarishta, a novel empirical formulation was prepared using combination of selected ingredients from these two formulations to support healthy heart functions and to reduce stress. Aim of the Study: Aim of the Study was to investigate herb-drug interaction (HDI) of Ridayarishta formulation through human hepatic cytochrome P450 (CYP450) enzyme inhibition assay. Materials and methods: Ridayarishta formulation was phyto-chemically standardized against arjunolic acid, arjunetin, berberine, piperine, resveratrol and withaferin-A using high performance thin layer chromatography (HPTLC) analysis. The formulation was standardized with respect to ethanol by gas chromatographic (GC) analysis. HDI was evaluated with Ridayarishta formulation and amlodipine besilate, atenolol, atorvastatin, metformin, glipizide glimepiride cocktail using high throughput CYP450 enzyme inhibition assay; against CYP1A2, 2C19, 2D6 and 3A4 isozymes. Results: Contents of arjunolic acid, arjunetin, berberine, piperine, resveratrol and withaferin-A in Ridayarishta formulation were found to be 1.76±0.12, 1.51±0.09, 1.85±0.05, 3.2±0.12, 1.21±0.08, and 2.16±0.09 ppm, respectively. Quantity of ethanol in Ridayarishta was found to be 7.95±0.023% (V/V). Ridayarishta showed significantly higher (P<0.001) IC50 value against CYP1A2 (IC50 –13.80±1.96 µg/mL), 2C19 (IC50 –14.343±2.28 µg/mL), 2D6 (IC50 –0.897±0.28 µg/mL) and 3A4 (IC50 –32.057±2.51 µg/mL) compared to positive controls such as furafylline, tranylcypromine, quinidine and ketoconazole respectively. Cocktail of herbal formulation and cardio protective, antihypertensive, anti-diabetic drugs showed significantly (P<0.001and P<0.01) less or negligible HDI. Conclusion: Ridayarishta formulation alone and cocktail with amlodipine besilate, atenolol, atorvastatin, metformin, glipizide, glimepiride had negligible or insignificant effect on CYP450 inhibition. It may be concluded that consumption of Ridayarishta along with selective cardio protective, antihypertensive and anti-diabetic conventional medicine is safe with negligible or without any significant CYP450 (CYP1A2, 2C19, 2D6 and 3A4) inhibition mediated HDI. Graphical abstract: